IL-7 During Antigenic Stimulation Using Allogeneic Dendritic Cells Promotes Expansion of CD45RA-CD62L+CD4+ Invariant NKT Cells With Th-2 Biased Cytokine Production Profile - Trujillo-Ocampo, Abel; Cho, Hyun-Woo; Clowers, Michael; Pareek, Sumedha; Ruiz-Vazquez, Wilfredo; Lee, Sung-Eun; Im, Jin S. (Frontiers in Immunology, 2020)
Invariant natural killer T (iNKT) cells are innate-like T lymphocytes cells that recognize glycolipid antigens associated with CD1d, non-classical antigen presenting proteins. They can drive either pro-inflammatory (Th-1) or anti-inflammatory (Th-2) immune microenvironment through the production of both Th-1 and Th-2 type cytokines upon activation, thus play a vital role in cancer, infection, and autoimmune diseases. Adoptive cell therapy using ex vivo expanded iNKT cells is a promising approach to enhance anti-tumor immunity or immunosuppression. However, overcoming phenotypic and functional heterogeneity and promoting in vivo persistency of iNKT cells remains to be a challenge. Here, we compared various methods for ex vivo expansion of human iNKT cells and assessed the quality of expansion, phenotype, and cytokine production profile of expanded iNKT cells. While a direct stimulation of iNKT cells in peripheral blood mononuclear cells with agonist glycolipid led to the expansion of iNKT cells in varying degrees, stimulation of enriched iNKT cells by irradiated autologous peripheral blood mononuclear cells or allogeneic dendritic cells resulted in consistent expansion of highly pure iNKT cells. Interestingly, the mode of antigenic stimulation influenced the dominant subtype of expanded iNKT cells. Further, we evaluated whether additional IL-7 or IL-15 during antigenic stimulation with allogeneic dendritic cells can improve the phenotypic heterogeneity and modify cytokine production profile of iNKT cells expanded from 18 consecutive donors. The presence of IL-7 or IL-15 during antigenic stimulation did not affect the fold of expansion or purity of expanded iNKT cells. However, IL-7, but not IL-15, led to a better expansion of CD4+ iNKT cells, enhanced Th-2 type cytokine production of CD4+ iNKT cells, and maintained the expansion of central memory (CD45RA-CD62L+) CD4+ iNKT cells. Our results suggest the addition of IL-7 during antigenic stimulation with allogeneic dendritic cells can promote the expansion of CD62L+Th-2+CD4+ human iNKT cells that can be used as novel immunotherapeutic to control excessive inflammation to treat various autoimmune diseases.